2009
DOI: 10.1016/j.ijnurstu.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Care and caring culture as experienced by nurses working in different care environments: A phenomenological–hermeneutic study

Abstract: The care and caring culture can be understood from the perspective of what it means to care and from the perspective of how care provision is accomplished. To attain a caring culture founded on certain values, for example caritas, love and charity, we must first understand how the organization and personnel understand caring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 22 publications
1
59
0
5
Order By: Relevance
“…37 Study findings also revealed that when the desired outcome of recovery is not achievable, health care professionals can provide a need-based spiritual and psychological care to comfort patients, protect their dignity, and enhance their quality of life. As the essence of nursing, [19][20][21] care is a holistic and patient-centered approach that focuses on all physical, mental, social, and spiritual aspects of patients' lives. 26,38 The aim of nursing is to provide care to patients in all situations even if there is little or no hope for recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Study findings also revealed that when the desired outcome of recovery is not achievable, health care professionals can provide a need-based spiritual and psychological care to comfort patients, protect their dignity, and enhance their quality of life. As the essence of nursing, [19][20][21] care is a holistic and patient-centered approach that focuses on all physical, mental, social, and spiritual aspects of patients' lives. 26,38 The aim of nursing is to provide care to patients in all situations even if there is little or no hope for recovery.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, care is considered as the essence and the core of nursing and it differentiates nursing from other fields of health care delivery. [19][20][21] Consequently, exploring nurses' attitudes toward and perceptions of futile care can help clarify the existing ambiguities.…”
mentioning
confidence: 99%
“…The informants had a desire to feel needed and have something meaningful to occupy themselves. Therefore, a major task for the network when establishing a caring culture is to invite older persons through someone who cares for them in a dignified way [51], so that the individual older person feels relaxed and secure in the caring situation [52]. In other words, the goal is to make things easier for other older people in the municipality who live at home, so that they, on basis of their own wishes and choice, can live their life as best they can [53].…”
Section: Self-esteem and Views Of Themselvesmentioning
confidence: 99%
“…One can be true to oneself in a way that mirrors one's 'caring ethos'. 4 Jakobsen and Sørlie believe working culture should be more open, especially when colleagues are concerned. They found that the ability to work under daily pressure was enhanced if the environment was open.…”
Section: Non-caring Cultures Versus Caring Culturesmentioning
confidence: 99%